Experimental and mathematical characterisation of the rheological instability of concentrated waste activated sludge subject to anaerobic digestion - Wei, Peng; Tan, Qiuman; Uijttewaal, Wim; van Lier, Jules B.; de Kreuk, Merle (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
•Yield-pseudoplastic behaviour with varying patterns in a wide shear rate range.•Improved characterisation by hybrid model fitting of defined shear rate segments.•Rheological model fitting reflected transient status but not intrinsic properties.•TS-related distinct flow status and transitions described rheological instability.•Measurement recommendations and a mathematical expression for sludge rheology. For a proper operational performance assessment of excess sewage sludge digesters in practice, a better understanding of waste activated sludge (WAS) rheological behaviour is important, especially regarding the low-shear and poor mixing zones in anaerobic digesters. The potential rheological instability of WAS with different total solids (TS) concentrations was studied in this research. The obtained yield-pseudoplastic behaviour showed varying patterns in a wide shear rate range, of which characterisation depended on hybrid model fitting of defined shear rate segments. Although a new mathematical expression improved the fitting quality, limited applicability of the empiric models reflected the samples’ transient rheological behaviour rather than intrinsic properties, challenging the included parameters definition. Characterised by the distinct flow status and transitions, the observed rheological instability gives more insight in viscoelastic and thixotropic effects on sludge flow and mixing behaviour in full-scale WAS treatment systems. Recommendations for developing a rheological measurement protocol were also formulated.